ELECTROCHEMICAL STUDIES ON MODIFIED ORGANO-SILANES COMPOSITE COATINGS FOR ALUMINIUM CORROSION INHIBITION - MAIOR, Ioana; CIOBOTARU, Ioana-Alina; CĂPRĂRESCU, Simona; COJOCARU, Anca; VĂIREANU, Dănuţ-Ionel (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The main objective of this study consists in developing a new anticorrosive protection coating for packaging industry based on deposition of organo-silanes composite film on the metallic material surface. Silane solutions (octyltrietoxysilane OTES and vyniltrietoxysilane VTES) modified with SiC and CeO2 nanoparticles were applied on a 99.99% aluminium substrate and compared with a sample of aluminium commercially available package (can). For the analysis of film composition and metal surface Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM) were performed. The results highlighted the film’s compactness and its adhesive properties, as well as the favourable effect of nanoparticles in tested coatings. Corrosion tests on aluminium samples with and without protective coatings, as well as on commercially available aluminium cans were carried out in phosphoric acid 3M using open circuit potential, potentiodynamic curves and Electrochemical Impedance Spectroscopy (EIS) techniques.